Some Bioactivities of Isolated Apigenin-7-O-glucoside and Luteolin-7-O-glucoside - Esen Sezen Karaoğlan; Hayrunisa Hancı; Mehmet Koca; Cavit Kazaz (Applied Sciences, 2023)
In this study, we aimed to isolate compounds from Stachys lavandulifolia (Lamiaceae) by chromatographic methods and perform tyrosinase, acetylcholinesterase, butyrylcholinesterase enzyme-inhibition and antimicrobial activity studies of these compounds by in vitro methods. In addition, a molecular docking study was planned for the molecule with the highest effect. Two flavone glycosides, apigenin-7-O-glucoside and luteolin-7-O-glucoside, were isolated from S. lavandulifolia. Both compounds were observed to be effective against Enterococcus faecalis, Klebsiella pneumoniae, and Staphylococcus aureus. The compounds showed weak tyrosinase and butyrylcholine esterase inhibition, while only luteolin-7-O-glucoside showed a more significant inhibitory effect against acetylcholinesterase (65 ± 2%). Therefore, molecular interactions between acetylcholinesterase and luteolin-7-O-glucoside were evaluated. In the docking study, it was observed that the molecule was bound to the enzyme with a low amount of free binding energy (Glide score: −8.31). As a result, the antibacterial effect of apigenin-7-O-glucoside and both antibacterial and acetylcholinesterase-inhibitory effects of luteolin-7-O-glucoside were determined.